Estimation of Ceruloplasmin activity, and copper, iron levels in Â·sera of nor1nal pregnants - AI-sarrag, N. F.; Rajab, T.M.A.; AJtai, W.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This  study  was undertaken  to shed light on the changes  of levels of CPactivity, Cu and  Fe in sera of .(53) normaJ non-smoker pregnant's  without complication, during  three1rimestcrs of pregnancy.G1  inc.l_ude  (I 8) pre nants in  the 1' 1 tri nester, G2 19)  pret:,rp:all.ts  _weartaken     m the  2"    tnmester  and  G3  (16) pregnants  m the  3rd  trunester./ othe.r ('18) Â·serum samples were taken from liealthy non-pregnant wqmenage matched as controlÂ·group G4.Results bowed a significant steady  elevation in CP .p:ctivity and  senm1Cu  with adv.auccd trimester  of  pregnancy compand  to control. The  ironconcentrations  in   the   sera   of   pregnant   women   shqwed a  s gnilicant reduction  compared  to control   roup also  a steady  decrease in Fe 1evels with advanced trimester wa.s lound.The  in .reasec..l activities   in  CP   as  Â·end